The effect of increased speaking rate and (intended) loudness on the glottal behaviour in stop consonant production as exemplified by Danish p - Andersen, Preben (Annual Report of the Institute of Phonetics University of Copenhagen, 1981)
The present combined fiberoptic-glottographic experiment has the purpose of studying the glottal behaviour in Danish stop consonant production at increased speaking rate and intended loudness, respectively. At increased speaking rate the degree and duration of the glottal abduction is found to decrease proportionally, i.e. the rate of the glottal abduction is constant, irrespective of speaking rate. Different individual strategies seem to be applied in the temporal organization of the glottal adduction. At increased intended loudness level no effect on the temporal organization of the gesture is observed, but the rate of glottal abduction is found to be faster. A model is proposed for the glottal behaviour under each of the two speech conditions. A very limited EMG-material (1 subject) shows changes in INT-activity under both conditions, whereas changes in PCA-activity occur only in connection with increased intended loudness level. The present findings concerning the speaking rate condition are compared to results from research on supraglottal articulatory organization at varying speaking rates.